¿Dónde está la mitología fenicia?: Al-Idrisi y los Aventureros de Lisboa - Matesanz Gascón, Roberto (Gerión. Revista de Historia Antigua, 2002)
Many archaelogical rests to attest the lengthy presence in the Iberian Peninsula of Phoenician settlements, and its deep impact on the native peoples material culture too. But is more difficult to determine what ideological consequences had the phoenician implantation. However, some stories preserved in the Middle Ages´ Spanish Literature show how beforehand, in the Ancient Ages, phoenician myths circulate through the Peninsula. An instance is the kabirim´s myth. The work of the Muslim geographer al-Idrisi shows us the kabirim like human beings, whose voyage is still remembered in Lisbon in the 12th century A.D.